2004
DOI: 10.1007/s11916-004-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Short-lasting headache syndromes and treatment options

Abstract: A number of primary headache syndromes are marked by their short duration of pain. Many of these syndromes have their own unique treatment, so they must be recognized by practicing physicians. In this article, a number of the short-lasting headache disorders are reviewed, including chronic paroxysmal hemicrania, SUNCT syndrome, hypnic headache, exploding head syndrome, primary stabbing headache, and cough headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
0
13
2
2
Order By: Relevance
“…It has been suggested that EHS is a rare clinical event (Ganguly et al, 2013), but others believe it to be under-reported (Pearce, 1989). It is thought to have a typical age of onset of over 50 years (Cohen and Kaube, 2004) and to be more common in females (Chakravarty, 2007;Rosen, 2004). However, no large-scale prevalence studies have been conducted, and most published articles report only very small numbers or individual case studies.…”
Section: Prevalence Ratesmentioning
confidence: 99%
“…It has been suggested that EHS is a rare clinical event (Ganguly et al, 2013), but others believe it to be under-reported (Pearce, 1989). It is thought to have a typical age of onset of over 50 years (Cohen and Kaube, 2004) and to be more common in females (Chakravarty, 2007;Rosen, 2004). However, no large-scale prevalence studies have been conducted, and most published articles report only very small numbers or individual case studies.…”
Section: Prevalence Ratesmentioning
confidence: 99%
“…PSH is generally thought to be a primary headache syndrome, onset at young age, predominantly in women, commonly associated with migraine or cluster headache and responsive to indomethacin (13–15). A recent population‐based study has shown that PSH is common in the general population (7, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Primer saplanma baş ağrısı indometazine cevaplı bir baş ağrısı sendromudur (3,11). Mekanizması tam bilinmese de indometazin'in beyin kan akımını ve BOS basıncını azaltarak etkili olduğu düşünülmektedir (12).…”
Section: Discussionunclassified